Global outlook : high intermediate reading - Bushell, Brenda; Dyer, Brenda (McGraw Hill, 2003)
"Global outlook is a two-book series designed to introduce learners to the basic reading skills required for fluent, accurate reading in English."--P. [4] of cover.